Antecedent Organizational Citizenship Behavior Model: a Literature Review - Rudi Yanto Batara Silalahi; Kampono Imam Yulianto; Dijan Mardiati; Sartono (Journal of Accounting and Finance Management, 2022)
Employee contributions that exceed their job descriptions or exceed the demands of their roles in the company are part of organizational citizenship behavior (OCB). Once the importance of OCB in achieving company goals makes us interested in research with the aim of providing recommendations for OCB antecedent models and solutions to these models at PT. Sejahtera Usaha Bersama (PT. SUB). This study uses a literature review method. Where the results of this study are recommendations for OCB antecedent models for PT. SUB, namely organizational communication, servant leadership, organizational commitment, job motivation, employee age, and organizational culture, it is hoped that these antecedents can strengthen the OCB dimensions, namely altruism, courtesy, sportsmanship, civic virtue and conscientiousness. And there are 6 solutions that we offer to PT. SUB.